Pengaruh Service Quality, Price, dan Service Recovery Terhadap Customer Loyality dengan Customer Satisfaction Sebagai Variabel Intervening (Studi Kasus pada Pelanggan Kereta Api Gajayana di Stasiun Kota Baru Malang) - Ego Andromega; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis purpose of this research was to determine and analize the effect of service recovery, price and service recovery on customer loyality through customer satisfaction on Gajayana train customers.. the research location was in Kota Baru Malang station with a population of all Gajayana train passengers in December 2018 of 5,549 people. From the population, samples were taken using the Slovin formula with a standard error of 10%, obtained by 98 respondents with criteria that had used Gajayana train service at least twice or had experienced disappointment. This type of research is explanatory research.               The analysis technique used in this study is quantitative and qualitative analysis. Quantitative testing includes validity test, reliability test, normality test, path analysis, significance test (t test) and sobel test. From the results of the analysis of calculations that have been carried out, it shows that there is a direct influence between service quality on customer loyalty through customer satisfaction of 0.339. Price on customer loyalty through customer satisfaction of 0.100. Service recovery for customer loyalty through customer satisfaction of 0.149. there is also an indirect effect between service quality on customer loyalty at 0.046, the indirect effect between price on customer loyalty is 0.128 and the indirect effect of service recovery on customer loyalty is 0.167. Keywords: service quality, price, service recoveri, customer satisfaction, customer loyality